化简√27-√12+√3/4=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 04:12:38
化简√27-√12+√3/4=化简√27-√12+√3/4=化简√27-√12+√3/4=(5√3)/4
化简√27-√12+√3/4=
化简√27-√12+√3/4=
化简√27-√12+√3/4=
(5√3)/4
化简√27-√12+√3/4=
√2+√8-√18=?3√3 -7√12 +4√27
化简 2√12+4√1/27-3√48-√4/3
√27+√12-√4/3
√12-√27+√3=
化简:1:√9*49 2::√16*7 3:√ 12/25 4::√27
化简:√12/√3=____
化简:√27-(2-√3)分之1-√12=
化简(1)√20+√5除以√5 -2 (2)√12+√27除以√3(3)(√3+√2)*(√3-√2)(4)2√12+3√48(5)√七分之一+√25-√700(6)√32-3√二分之一+√2
化简:√32-3√1/2-√1/8 (2)(√32+√27)/√2+(√12+√27)×√3
2√12-4√1/27+3√48
2√12-4√1/27+3√48
9√(3+7√(12-4√(27 急
5√96+2√24-5√12+3√27+4√4/3
计算:√4-√3/√12+√3-√2/√6+√2-√1/√2=?
化简:√18-√8;(√3+1)²计算:(√2+1)(√2-1);√16+√0.25-³√27;√20+√5-2√5;√12+√48-3√1/3
√27-√12+√3/1
√27+√12/√3